Surgical Treatment of Lateral Malleolar Fractures Using the Compression Cerclage System - (:unkn) unknown (AMER PODIATRIC MED ASSOC, 2016)
Background: Lateral malleolar fractures (Weber type B or OTA 44-B) account for 60% of all ankle fractures. To achieve anatomic restoration, surgical stabilization provides better results than conservative treatment. Various fixation methods are available to treat these fractures; however, the best method is still unknown. Our objectives were to present a new, useful, and efficient surgical technique for stabilizing lateral malleolar fractures and to analyze the outcomes of patients treated with the compression cerclage system. Methods: The surgical technique consists of a Kirschner wire that is passed percutaneously and perpendicular to the fracture line, and a cerclage wire that is passed in a semi-circular fashion over the ends of the Kirschner wire on the lateral side of the bone, leaving loops on each side to allow bilateral compression while twisting both wires. We retrospectively evaluated patients treated with this technique, with or without additional fractures. Follow-up of <24 months and bilateral ankle fractures were the exclusion criteria. Fractures were examined clinically and radiologically in comparison to the uninjured side and were rated according to the criteria reported by McLennon and Ungersma. Olerud and Molander ankle score was used to evaluate functional outcome. Results: At the final follow-up, 15 out of 21 patients (9 women and 6 men; mean age, 48.2 years [range, 19-78 years]) were evaluated. The mean follow-up was 5.16 years (28-129 months). Five patients had an isolated lateral malleolar fracture; eight had lateral and medial malleolar fractures; and two had trimalleolar fractures. At the final follow-up, 11 patients were rated good functionally and four were fair, and all patients were rated good radiographically according to the criteria by McLennon and Ungersma. Mean Olerud and Molander ankle score was 93.3 (range, 80-100). Conclusions: The compression cerclage system provides good functional and radiological outcomes in patients with lateral malleolus fractures. This method is useful, safe, and efficient with minimum hardware. It can be applied through limited soft-tissue stripping, which is especially important in patients with a high risk for wound complications.
Keywords: ANKLE FRACTURES; OPERATIVE TREATMENT; WEIGHT-BEARING; LAG SCREW; FIXATION; OSTEOSYNTHESIS; PLATE